Prevalence of delusions in drug‐naïve Alzheimer disease patients: A meta‐analysis. (11th October 2017) - Lai, Leo; Lee, Philip E.; Chan, Peter; Fok, Mark C.; Hsiung, Ging‐Yuek R.; Sepehry, Amir A.
Abstract : Introduction: Neuropsychiatric symptoms (NPS) are common at all stages of Alzheimer disease (AD). Delusions in AD are associated with negative clinical consequences and may signal rapid disease progression. Hence, we sought to determine the prevalence of delusions in drug‐naïve (no cholinesterase inhibitor or neuroleptic medications) AD patients. Methods: In this meta‐analysis, a search of the EMBASE, MEDLINE, and PsycINFO databases was performed. We selected studies reporting delusion prevalence measured by the Neuropsychiatric Inventory (NPI) in drug‐naïve AD patients. An aggregate delusion event rate with 95% confidence interval (CI) was calculated. The I 2 statistic was used to assess the magnitude of between‐study heterogeneity. Single variable meta‐regressions allowed examination of the effect of moderating factors and heterogeneity. Quantitative measures were used to appraise for publication bias. Results: We identified 6 studies with 591 participants allowing calculation of the aggregate delusional prevalence rate. Irrespective of dementia severity, the aggregate event rate for delusions was 29.1% (95% CI: 20–41%; I 2  = 84.59). No publication bias was observed. Conclusion: This meta‐analysis calculates a 29.1% prevalence rate of delusions in AD patients. There is a trend towards increasing delusion prevalence in concordance with increasing severity of dementia. Given delusions are associated with poorer outcomes, the obtained prevalence should motivate clinicians to screen carefully for delusions. Current literature limitations warrant future studies, with sub‐analyses on dementia severity, and other neurobiological factors known to influence the presence of delusions.